RESOURCE CHARACTERISTICS OF THE PENAEID PRAWN PARAPENAEOPSIS STYLIFERA IN MANGALORE COAST - Ramamurthy, S (Indian Journal of Fisheries, 2011)
Some aspects of the populat'on characteristics of the prawn Parapenaeopsisstylifera from 1962 in the Mangalore coast are presented. The fishery experiencedwide annual variations with two peaks in general, the primary one during April-May, the ancillary being during November-December. The maximum sustainableyield is oalculated to be 448 tonnes corresponding to an effort of approxdmately32,000 boat days. The fishery was predominantly composed of size groups rangingfrom 73 to 93 mm and 83toll3 mmamong males and females respectively. Recruitmentof smaller size groups was noticed mostly during Novembeir-December and'iMarch-April. The maximum number of broods that could be noticed in a seasonw.'s six. Growth studies indicated that males and femaks attain a length of 90/95and 110/125 mm at the end of one and two years respectively. In the case ofmales, the late 0-year class predominated whereas in irespect of females, eitherthe late 0-year or one-year class was found to be predominsmt. The mean lengthshowed considerable annual variations which appear to be due to natural causes.Females preponderated in fll the years except 1962-63. The average annualinstantaneous rate of mortality for females between one and two year olds wasestimated to be 4.28.